2012
DOI: 10.2172/1122332
|View full text |Cite
|
Sign up to set email alerts
|

Initial proof-of-principle for near room temperature Xe and Kr separation from air with MOFs

Abstract: SUMMARYMaterials were developed and tested in support of the U.S. Department of Energy's Office of Nuclear Energy, Fuel Cycle Technology Separations and Waste Forms Campaign. Specifically, materials are being developed for the removal of xenon (Xe) and krypton (Kr) from gaseous products of nuclear fuel treatment.During fiscal year 2012, three metal organic framework (MOF) structures were investigated in greater detail for the removal and storage of Xe and Kr from air at room temperature. Breakthrough measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This observation is supported further by molecular simulations in which MOFs, with pore-limiting diameters slightly above the kinetic diameters of Xe and Kr, are shown to have high Xe/Kr selectivities . Among all the MOF materials tested, Ni/DOBDC and a partially fluorinated MOF with copper (FMOF-Cu) have shown improved Xe and Kr capacities at room temperature relative to previous materials. ,,, Xe at parts per million (ppm) concentrations have been removed from air at room temperature with Ni/DOBDC and FMOF-Cu, and the selectivity of FMOF-Cu was found to change from Xe > Kr to Xe < Kr simply by changing the temperature. Herein we demonstrate the removal of Xe and Kr from air and from each other with a two-column breakthrough approach at a noncryogenic temperature.…”
Section: Introductionmentioning
confidence: 74%
“…This observation is supported further by molecular simulations in which MOFs, with pore-limiting diameters slightly above the kinetic diameters of Xe and Kr, are shown to have high Xe/Kr selectivities . Among all the MOF materials tested, Ni/DOBDC and a partially fluorinated MOF with copper (FMOF-Cu) have shown improved Xe and Kr capacities at room temperature relative to previous materials. ,,, Xe at parts per million (ppm) concentrations have been removed from air at room temperature with Ni/DOBDC and FMOF-Cu, and the selectivity of FMOF-Cu was found to change from Xe > Kr to Xe < Kr simply by changing the temperature. Herein we demonstrate the removal of Xe and Kr from air and from each other with a two-column breakthrough approach at a noncryogenic temperature.…”
Section: Introductionmentioning
confidence: 74%
“…Many reports discuss thermal, chemical, and mechanical stability of MOFs, yet relatively few examine their radiation stability. , Furthermore, results of previous studies are difficult to compare as they are collectively scattered in both MOF selection and irradiation methodology (see Table S1) and could benefit from more systematic approaches with well-defined variables. Pinpoint studies of irradiated MOFs have observed general reduction in crystallinity, surface roughening, and, where accessible, changes in the apparent surface area. ,,, Volkringer et al describe a gamma irradiation study of model MOFsZIF-8, HKUST-1, MILs (MIL-53, MIL-100, and MIL-120), and UiO-66.…”
Section: Introductionmentioning
confidence: 99%